The relationship between body image and tea drinking habits with anemia among adolescent girls in Badung District, Bali, Indonesia - Kadek Agus Dwija Putra; Putu Cintya Denny Yuliyatni; Ni Ketut Sutiari (Universitas Udayana, 2020)
Background and purpose: The prevalence of anemia among adolescent girls in Indonesia remains high. Poor nutrition is a risk factor of anemia among adolescent girls, which is likely related to food intake restrictions to achieve a desired body shape (body image), and the habit of drinking tea while eating which can affect the absorption of iron. This study aims to determine the relationship between anemia with body image perception and tea drinking habits among adolescent girls. Methods: This study used a cross-sectional design carried out from March-May 2018, involving girls aged 15-18 years at high schools in Badung District. Two schools were selected from 44 high schools, then a sample of 106 students were selected by systematic random sampling. Data collected included hemoglobin levels measured with hematology autoanalyzer, nutritional status with anthropometric measurements, and data on socio-demographics, socio-economics, tea drinking and eating habits, menstrual pattern, helminthiasis, knowledge and perception of body image with face-to-face individual interviews. Data were analyzed using the Chi square test for bivariate analysis, and multivariate using logistic regression. Results: The prevalence of anemia (hemoglobin <12 g/dL) in adolescent girls was 13.2%. The results of the logistic regression analysis showed that the variables associated with anemia were poor knowledge about anemia with an adjusted odds ratio (AOR)=11.4 (95%CI: 1.6-83.1), no iron supplement consumption (AOR=14.7; 95%CI: 1.9-109.8), negative body image (AOR=30.6; 95%CI: 2.9-321.1), tea drinking habits while eating (AOR=52.2; 95%CI: 4.2-642.9) and excessive menstrual volume (AOR=17.1; 95%CI: 1.6-185.9). Conclusion: Negative perceptions of body image and tea drinking habits while eating increase the risk of anemia among adolescent girls aged 15-18 years. In addition, poor knowledge about anemia, a history of not consuming iron supplements and excessive menstrual volume can also increase the risk. These factors need to be considered when designing policies to reduce anemia among adolescent girls.